(untitled) (Research, Society and Development, 2022)
Canine Visceral Leishmaniasis (CVL) is considered an endemic disease in several regions of Brazil, being the focus of several public policies because of its zoonotic potential. The only medication regulated by the Ministry of Agriculture, Livestock and Supply (MAPA) in the country for the treatment of the disease in animals is miltefosine. Thus, the search for innovative drugs is necessary, some of which are already in phases of laboratory trials and others have been indicated for use in clinical routine in other countries. Therefore, the objective of the present study was to highlight the therapeutic possibilities against CVL, trying to emphasize, mainly, the new drugs frequently used in clinical routine, as well as those that have the potential to become viable options for the approach of CVL in Brazil. For the review, we implemented a manual systematic search in the main scientific databases, using indexers related to the theme in the period from 1994 to 2022. The results of the systematic search revealed that the therapeutic options potentially active against Leishmania infantum include marbofloxacin, beta-glucans, immunomodulators, and essential oils from medicinal plants and their derivative compounds, which are considered promising candidates for the treatment and control of CVL. Therefore, from the data gathered, it was possible to verify that there are many studies about the therapeutics of the disease and that understanding them can be decisive in providing good care to the sick animal, as well as in the implementation of an adequate drug planning.